A flexible recyclable self-cleaning substrate based on a polymer-plasmonic hybrid composite - Ahmed T. Alanazi; Mahdi Alqahtani; James H. Rice (Results in Materials, 2023)
The formation of nanocomposites including metals and organic conducting semiconductors offers significant potential to act as an effective flexible, lightweight platform that can support plasmon-based sensing. We demonstrate super band-gap irradiation of a polymer-plasmonic composite based upon the conducting polymers P3HT and PCBM to support the plasmon-enhanced based spectroscopic detection and then the removal of analytes. We demonstrate that such a polymer-plasmonic composite is an effective self-cleaning substrate for application as a reusable optical sensing substrate.